A new jawfish of the genus Opistognathus (Perciformes: Opistognathidae) from Japan - Shinohara, Gento (Zootaxa, 2021)
A new species of jawfish, Opistognathus ocellicaudatus, is described based on a single specimen collected at 67 m depth in Sagami Bay (near the mouth of Tokyo Bay), Honshu Island, Japan. The new species can be separated from all other Indo-West Pacific jawfish species in having 3 longitudinal dark brown stripes on the body, a large dark whitish-rimmed ocellus on the caudal fin, a small black blotch on the opercular flap, the dorsal fin with 11 spines and 11 soft rays, the anal fin with 2 spines and 11 soft rays, 21 pectoral-fin soft rays, 26 vertebrae, 42 oblique scale rows, and 2 supraneurals. The holotype is a female containing mature eggs, suggesting summer spawning. The type locality was close to the northern distributional limit of Opistognathidae in the Indo-West Pacific. [http://zoobank.org/urn:lsid:zoobank.org:act:00DCADDA-BE92-4C33-B7EB-1DA8348BA02A]